Determinants of Accounting Fraud Tendency in Lpd: A Study From The Perspective of Internal Factors in Badung Regency - I Gede Bayu Saputra; I Wayan Suartana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze internal factors that influence the tendency of accounting fraud in Village Credit Institutions (Lembaga Perkreditan Desa/LPD) in Badung Regency. The research is based on the fraud triangle theory, which highlights conditions that may trigger fraudulent behavior. A quantitative approach was employed, with data collected through questionnaires distributed to the heads and treasurers of each LPD. The study population consisted of 115 LPDs, with a sample of 54 LPDs selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 26 to examine the effects of internal control, human resource competence, compliance with accounting rules, and ethical organizational culture on the tendency of accounting fraud. The results indicate that internal control, human resource competence, compliance with accounting standards, and ethical organizational culture all have a negative and significant effect on the tendency of accounting fraud. These findings underscore the importance of strengthening internal controls, enhancing employee competence, adhering to accounting standards, and fostering an ethical organizational culture to minimize the occurrence of accounting fraud in LPD financial management.